2013
DOI: 10.1007/s11307-013-0664-5
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Stroke-Induced Neuroinflammation in Mice Using [18F]PBR06

Abstract: Purpose The purpose of this study is to evaluate the 18 kDa translocator protein (TSPO) radioligand [18F]N-fluoroacetyl-N-(2,5-dimethoxybenzyl)-2-phenoxyaniline ([18F]PBR06) as a positron emission tomography (PET) imaging biomarker of stroke-induced neuroinflammation in a rodent model. Procedures Stroke was induced by transient middle cerebral artery occlusion in Balb/c mice. Dynamic PET/CT imaging with displacement and preblocking using PK111195 was performed 3 days later. PET data were correlated with immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Besides, the present study showed a relatively earlier TSPO overexpression in comparison to previous studies. 2,11,19,20 These differences may be related to differential pattern of leukocyte infiltration depending on the mice model of cerebral ischemia used. 21 According to this study, mice subjected to permanent MCAO showed both an earlier and extensive neuroinflammatory reaction than mice subjected to transient models of MCAO.…”
Section: /Cd11bmentioning
confidence: 99%
“…Besides, the present study showed a relatively earlier TSPO overexpression in comparison to previous studies. 2,11,19,20 These differences may be related to differential pattern of leukocyte infiltration depending on the mice model of cerebral ischemia used. 21 According to this study, mice subjected to permanent MCAO showed both an earlier and extensive neuroinflammatory reaction than mice subjected to transient models of MCAO.…”
Section: /Cd11bmentioning
confidence: 99%
“…MCAO procedure was described as previously [3]. Briefly a silicon suture (Doccol Corporation, MA) occluded the perfusion in the left MCA for 60 min, followed by removal of the suture and terminal ligation of the left carotid artery.…”
Section: Mouse Model Of Middle Cerebral Artery Occlusion (Mcao)mentioning
confidence: 99%
“…With our previously reported MCAO techniques inducing focal cerebral ischemia in mice [3], we combined ICW techniques in these animals to perform in vivo TPM imaging [ Fig. 1(a)].…”
Section: Visualizing Activated Microglia In a Mouse Model Of Focal Cementioning
confidence: 99%
See 2 more Smart Citations